Analisis Perencanaan Pembelajaran Jarak Jauh pada Mata Pelajaran Fiqih dalam Meningkatkan Kualitas Pembelajaran (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to analyze the form of PJJ funding for fiqh subjects in improving the quality of learning. In the implementation of PJJ there are several challenges and obstacles. Among the challenges faced by teachers, teachers are required to think creatively and innovatively in providing online learning. Parents during online learning are needed by children. Some of the obstacles that often arise include limited internet access, lack of direct interaction between teachers and students, and difficulties in conducting comprehensive learning evaluations. The type of research used is field research. The method used in this research is qualitative research. Data sources were obtained through interviews, documentation, and observation. The results of this study Distance learning planning (PJJ) in fiqh subjects at MTsN 4 Padang Pariaman can be said to be not optimal. This is evidenced by not all Fiqh teachers at MTsN 4 Padang Pariaman have complete learning tools, but all fiqh teachers have lesson plans. Of the two resource persons of fiqh subject teachers at MTsN 4 Padang Pariaman, only one fiqh subject teacher has a complete learning tool, namely Mr. Hafizuddin Hasan in the preparation of lesson plans, it is still not 100% in line with the reality in the field